Update on Essential Hypertension (IntechOpen, 2016)
Essential hypertension is a quantitative characteristic that is important for correlating with the rate of morbidity and mortality in the developed and developing countries. The etiology of essential hypertension is complex. This work, authored by renowned researchers in the field, gives updated concepts about essential hypertension. Novel advanced topics are presented in a sole document as hypertension in children; the contribution in the psychiatric comorbidities associated with it; mechanisms of omega-3 in protection against hypertension-related organ damage; oxidative stress at different levels; genetics-associated studies; the role of pollution in essential hypertension; personalized healthcare in a hypertensive patient; and hypertension-related disparities between ethnic groups. It can conclude so that essential hypertension is one of the hottest topics in contemporary medicine.